Out of sight, but no longer out of mind – towards an increased recognition of the role of soil microbes in plant speciation. Issue 3 (15th January 2018) - Geml, József; Wagner, Maggie R.
Abstract : This article is a Commentary onOsborne et al ., 217 : 1254–1266.